Synthesis and Characterization of Hydroxyapatite from Duck Eggshell by Wet Precipitation Process - Yelmida Azis; Cory Dian Alfarisi; Komalasari Komalasari; Khairat Khairat; Yusnimar Sahan (Journal of Applied Materials and Technology, 2021)
Hydroxyapatite (HAp, Ca10(PO4)6(OH)2) is the most stable form of calcium phosphate and widely used in various medical applications, mainly in orthopedics and dentistry due to its close similarities with the inorganic mineral component of bone and teeth. This study aims to synthesize hydroxyapatite from duck eggshell using the precipitation method. The duck eggshell was calcined, hydrated (slaking) and underwent carbonation to form Precipitated Calcium Carbonate (PCC).  Afterwards, (NH4)2HPO4 was added to produce HAp by varying the molar ratio of Ca/P by 1.67, 1.77 and 1.87 and stirring speed by 200, 250, 300rpm under basic condition (pH 10 – 11). The best results were obtained at a molar ratio of 1.77 with 200rpm stirring speed. Furthermore, the X-ray Diffraction (XRD) analysis showed that its crystals were hexagonal with sizes of 23.062nm, in the absence of other crystalline phases. Therefore, the hydroxyapatite was obtained in the agglomerates form with a specific surface area of ??55.929m2/g.